(untitled) (Annals of Medical Research, 2021)
Aim: In this study, we aimed to evaluate retrospectively uric acid and uric acid / high-density lipoprotein (HDL) ratio in patients with coronary artery fistula who underwent coronary angiography in our cardiology clinic. Coronary artery fistulas (CAF) are seen most often congenitally but also may be acquired and often encounter an asymptomatic clinic. In chronic diseases, e.g., chronic kidney disease, metabolic syndrome, a decrease in HDL is observed, while high uric acid levels have been associated with adverse events.Material and Methods: A total of 111 patients were included in the study, including 46 patients with coronary fistula and 65 controls with normal coronary arteries. Demographic data, laboratory parameters and structural features of the fistula were recorded. Transthoracic echocardiography was performed in all patients.Results: Baseline characteristics were similar between the groups. Previous medications were similar between the two groups. Uric acid [5.9 (4.0-8.0) vs. 4.5 (3.5-8.3)) and uric acid / HDL ratio (14 (7-30) vs. 10 (5-32)] were found to be significantly higher in the fistula group (p 0.001). The creatinine, fasting glucose, cholesterol panel, and hemogram parameters were not significantly different between the groups. Right ventricular end-diastolic (RVED) diameter was significantly higher in CAF group (2.68±0.79, 2.50±0.35; p=0.03). The other echocardiographic measurements were not significantly different between the two groups. Conclusion: The uric acid and uric acid / HDL ratio (UHR), which we can easily look at in peripheral blood, were found to be significantly elevated in fistula patients compared to the control group. The clinical significance of the result could be supported by large-scale studies in the future.